Tobacco, alcohol use and other risk factors for developing symptomatic COVID-19 vs asymptomatic SARS-CoV-2 infection: a case–control study from western Rajasthan, India - Saurabh, Suman (Trans R Soc Trop Med Hyg, 2021)
BACKGROUND: Understanding risk factors of symptomatic coronavirus disease 2019 (COVID-19) vis-à-vis asymptomatic severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection, severe disease and death is important. METHODS: An unmatched case–control study was conducted through telephonic interviews among individuals who tested positive for SARS-CoV-2 in Jodhpur, India from 23 March to 20 July 2020. Contact history, comorbidities and tobacco and alcohol use were elicited using standard tools. RESULTS: Among 911 SARS-CoV-2-infected individuals, 47.5% were symptomatic, 14.1% had severe COVID-19 and 41 (4.5%) died. Older age, working outside the home, cardiac and respiratory comorbidity and alcohol use were found to increase the risk of symptomatic disease as compared with asymptomatic infection. Current tobacco smoking (odds ratio [OR] 0.46 [95% confidence interval CI 0.26 to 0.78]) but not smokeless tobacco use (OR 0.81 [95% CI 0.55 to 1.19]) appeared to reduce the risk of symptomatic disease. Age ≥60 y and renal comorbidity were significantly associated with severe COVID-19. Age ≥60 y and respiratory and cardiac comorbidity were found to predispose to mortality. CONCLUSIONS: The apparent reduced risk of symptomatic COVID-19 among tobacco smokers could be due to residual confounding owing to unknown factors, while acknowledging the limitation of recall bias. Cross-protection afforded by frequent upper respiratory tract infection among tobacco smokers could explain why a similar association was not found for smokeless tobacco use, thereby being more plausible than the ‘nicotinic hypothesis’. Those with comorbidities and age ≥60 y should be prioritized for hospital admission.